Analysis of factors affecting the satisfaction of Sharia stock investors in Bangka Belitung and Riau, Indonesia - Abadi, Firman; Wicaksono, Muhammad Adi (Universitas Islam Indonesia, 2024)
IntroductionThe Indonesian Sharia stock market has experienced significant growth, reflecting increasing demand for ethical investment options that align with Islamic principles. Despite this expansion, limited research has explored the factors influencing investor satisfaction in Sharia-compliant markets, particularly the role of behavioral traits and financial literacy alongside adherence to Sharia values.ObjectivesThis study examines the interplay between Sharia values, financial literacy, behavioral traits (overconfidence, self-efficacy, herding behavior, and risk tolerance), and investment decisions in determining investor satisfaction in the Indonesian Sharia stock market.MethodA quantitative explanatory research design was employed, gathering data from 151 individual Sharia stock investors in Bangka Belitung and Riau provinces through online surveys. Structural Equation Modeling (SEM) was used to analyze relationships among variables, including sharia values, behavioral traits, financial literacy, investment decisions, and investor satisfaction.ResultsThe findings reveal that sharia values are the strongest determinant of investor satisfaction, emphasizing the importance of ethical alignment. Behavioral traits, particularly overconfidence and self-efficacy, positively influence investment decisions mediating satisfaction. Financial literacy, herding behavior, and risk tolerance exhibit limited or indirect effects on satisfaction, highlighting the complex dynamics of Sharia-compliant investing.ImplicationsThe study underscores the critical role of ethical principles and behavioral traits in shaping satisfaction within sharia markets. It provides practical insights for financial institutions, policymakers, and educators to design more effective investment strategies and educational programs.Originality/NoveltyThis research integrates behavioral finance and Sharia principles, contributing to the growing literature on ethical investing. The study offers a comprehensive framework for understanding investor satisfaction, providing a foundation for future research and practical applications in Sharia-compliant markets.